Harmonization of Regulations Regarding Social Media Used for Political Communication for the Establishment of Clean and Conducive Elections - Anggriawan, Teddy Prima; Mahanani, Anajeng Esri Edhi (Law Research Review Quarterly, 2018)
The development of information technology have been used to simplify the people to get fast access of information, especially after the modernization community has cheered the various convenience and entertainment offered by social media. The speed of media access, in this case is not always directly proportional to the accuracy of information, it can be said that social media was not able to provides the quantity of information without ascertaining the right quality of information. The problem appears while the Law Number 7 of 2017 about the election then provide an opportunity for election participants to utilize social media for the advantage of the campaign, on article 275 of the a quo law. This provision certainly also accommodates the interests of people in democratic countries. This study aims to collect legislation governing social media, to be harmonized with the provisions of the article that governs the campaign media, given that social media is very effective for campaign media, but still must be given by legal restrictions. This discussion will be analyzed by using the normative method through document study. Based on the discussion, it can be formulated as follows; First, that social media is very effective to be used by political parties to carry out the functions of political communication, especially campaigns aimed at gaining milineal generation "votes". Second, harmonization of campaign arrangements through social media will help conduct elections that are conducive without hoaxes and mass duping due to the development of information technology.